STRATEGI PENGEMBANGAN DESA SILALAHI II SEBAGAI DESTINASI WISATA RAMAH WISATAWAN PASCA PANDEMI COVID-19 - Dina Yunita (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
Abstract Dairi Regency Government through Dairi Regency Regent Decree No. 83/556/II/2022 stipulates the silalahi tourism village as a tourist village to be developed as part of the Toba Caldera UNESCO Global Geopark. Silalahi II tourism village and its surroundings are tourist attractions that can be developed by relying on the existing tourism potential. In addition to the enchanting natural charm, Silalahi II Tourism Village has traditional and cultural tourism owned by Raja Silahisabungan who has descendants of 8 clans, namely in the form of sites, local cultural wisdom which is held in the Marga People's Party every year and separate ceremonial events by the local community. The development of natural and cultural tourist attractions is carried out by paying attention to aspects of the beauty and quality of tourism as a post-covid-19 tourism trend. This research was conducted using descriptive qualitative method with SWOT strategy analysis.